Apoptosis-Induced Chromosomal Rearrangements as a Driver of Genomic Instability in Cancer. Preprint posted on Authorea, a platform operated by Atypon (a Wiley company), September 19, 2025. - Sang Nee, Tan
This article systematically synthesizes published evidence to propose a new conceptual model of apoptosis-induced chromosomal rearrangements as a driver of genomic instability in cancer. Nasopharyngeal carcinoma (NPC) is characterized by recurrent chromosomal aberrations, yet the origins of these structural mutations remain poorly understood. Emerging evidence supports a model in which oxidative stress and inflammatory stimuli—hallmarks of NPC pathogenesis—trigger apoptosis in nasopharyngeal epithelial cells, activating caspase-activated DNase (CAD). CAD preferentially cleaves DNA at matrix association region/scaffold attachment region (MAR/SAR) sites that anchor chromatin to the nuclear scaffold. When cells escape complete apoptotic execution (a process termed anastasis), these CAD-induced double-strand breaks (DSBs) are repaired by error-prone end joining pathways—classical non-homologous end joining (NHEJ) and, more commonly, microhomology-mediated end joining (MMEJ), a variant characterized by short microhomologies. The outcome is a spectrum of chromosomal rearrangements that recurrently map to MAR/SAR-enriched fragile sites. This synthesis reframes cancer mutagenesis not as a random consequence of genomic instability, but as a structured outcome of subverted cell death programs. It integrates mechanistic and genomic studies in NPC with broader evidence from other inflammation- and virus-associated cancers, including Barrett’s esophagus–derived esophageal adenocarcinoma, gastric cancer, hepatocellular carcinoma, bladder cancer, and EBV-associated lymphomas, as well as hematologic malignancies involving MLL (KMT2A) fusions. Beyond mechanism, this model has translational implications. Structural variant hotspots defined by apoptotic cleavage may guide biomarker discovery, while the unique dependencies of apoptosis-survivor cells highlight therapeutic opportunities. These include targeting DNA polymerase Theta to block MMEJ, enforcing complete apoptotic execution to prevent mutagenic survival, exploiting checkpoint vulnerabilities (ATR/CHK1), and preventive strategies to limit chronic inflammation or viral load. Finally, future directions include validating apoptosis-linked rearrangements in patient tumors through breakpoint mapping, microhomology analysis, and cell-free DNA (cfDNA) profiling, and extending investigations to single-cell and genome-wide mapping approaches. Overall, this synthesis represents a conceptual advance by reframing cancer mutagenesis as a structured outcome of subverted cell death programs rather than random genomic instability.